2019
DOI: 10.1111/anae.14610
|View full text |Cite
|
Sign up to set email alerts
|

Adverse side‐effects of dexamethasone in surgical patients – an abridged Cochrane systematic review

Abstract: In the peri-operative period, dexamethasone is widely and effectively used for prophylaxis of postoperative nausea and vomiting. The objective of this meta-analysis was to assess the adverse effects of an incidental steroid load of dexamethasone in adult surgical patients. We searched in MEDLINE, Embase, the Cochrane Central Register of Controlled Trials and the Web of Science for randomised controlled trials comparing an incidental steroid load of dexamethasone with a control intervention in adult patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 67 publications
(204 reference statements)
6
71
1
6
Order By: Relevance
“…Corticosteroid associated hyperglycemia may have a pronounced peak glucose concentration after 9 to 12 hours [8,23], and gradually decrease to baseline or to normal after nocturnal period [11]. However, in this study, we did not observe a discernable trend of glycemic decrease from afternoon to next morning.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Corticosteroid associated hyperglycemia may have a pronounced peak glucose concentration after 9 to 12 hours [8,23], and gradually decrease to baseline or to normal after nocturnal period [11]. However, in this study, we did not observe a discernable trend of glycemic decrease from afternoon to next morning.…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, the higher incidence of glucocorticoid induced diabetes may signi cantly decrease after 30 months [6]. The magnitude and duration of dexamethasone induced glucose level increase may be mild and transient in patients without diabetes [7,8]. Importantly, researchers observed that patients without prior history of diabetes showing a comparable [9], or greater increase in glucose levels compared to those of patients with onset diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…No evidence currently exists correlating dexamethasone use with an increased occurrence of postoperative wound infection or wound healing delay. 61 …”
Section: Dexamethasonementioning
confidence: 99%
“…4 Dexamethasone has been associated with an increase in postoperative blood glucose concentration in diabetic and non-diabetic patients. 5 Concerns about the potential to cause delayed wound healing and systemic or wound infection have not been confirmed in a recent meta-analysis. In one RCT, the increase in mean serum glucose concentrations with perineural dexamethasone administration was clinically insignificant.…”
Section: Steroids Dexamethasonementioning
confidence: 99%